WASH and learn: a scoping review of health, education and gender equity outcomes of school-based water, sanitation and hygiene in low-income and middle-income countries - Robert Dreibelbis; Kondwani Chidziwisano; Clara MacLeod; Laura Braun; Jenala Chipungu; Sarah Bick; Katherine Davies; Mwamba Mwenge (BMJ Global Health)
School-age children in low-income and middle-income countries (LMICs) face health and educational challenges due to inadequate water, sanitation and hygiene (WASH) in schools (WinS). Evidence for the impact of WinS interventions is limited and inconsistent, and previous systematic reviews have faced challenges in synthesising data due to varied interventions, study designs and outcome measures, although most do not examine this variability in more detail. This scoping review identified 83 experimental studies from 33 LMICs measuring a primary or secondary health or educational outcome among pupils, published up to November 2023, using a systematic search of seven databases and searching of reference lists of previous systematic reviews and included articles. These included 65 studies (78%) not included in previous WinS reviews and encompassed 313 intervention effects across 14 outcome domains. Interventions comprised an array of WASH technologies and approaches, often combining infrastructure and behaviour change methods and frequently integrated with other school-based initiatives like deworming. 36 studies (43%) measured only behavioural or knowledge outcomes. Our comprehensive inventory of study outcomes identified 158 unique outcome measures, with 72% measured in exactly one study. Common outcomes included parasitic infections, anthropometric measures and school absence, but approaches to measurement varied widely even for similar outcomes. Only 7% of results were disaggregated by gender, limiting assessment of differential impacts. Our findings underscore the need for standardised outcome measures in WinS research incorporating a complete definition of the assessment and aggregation approach, greater attention to gender-specific impacts, and further exploration of modalities and functions of WinS interventions alongside novel meta-analysis methods to disentangle effects of diverse intervention components.